Determinación de la edad de Istiophorus platypterus (Pisces: Istiophoridae) al sur del Golfo de California, México - Alvarado-Castillo, Reyna M; Félix-Uraga, Roberto (Revista de Biología Tropical, 1996)
Specimens (973) of the sailfish Istiophorus platypterus caught by sport fishing in the southern of the Gulf California from 1989 to 1991 were measured. The fourth spine of the dorsal fin of 745 specimens were also collected to estimate age and growth based on observations of a transyerse section. We were able to read the opaque and translucent bands of 97% of the sections. A monthly analysis of the type of edge, opaque or translucent, indicated that the formation of an opaque band from a hialine one takes one year. Thus, we were able to estimate the numbers in age groups from O to 7. The most abundant age groups were, in order 3, 2 and 4. The majority of!be specimens were between 180 and 210 cm in body length.